Proceedings of the 2001 IEEE Workshop on the Applications of Signal Processing to Audio and Acoustics (Cat. No.01TH8575)
DOI: 10.1109/aspaa.2001.969546
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Kalman filtering for the harmonic plus noise model

Abstract: We present a probabilistic description of the Harmonic plus Noise Model (HNM) for speech signals. This probabilistic formulation permits Maximum Likelihood (ML) parameter estimation and speech synthesis becomes a straightforward sampling from a distribution. It also permits development of a Kalman filter that tracks model parameters such as pitch, harmonic amplitudes, and autoregressive coefficients. We focus here on pitch tracking for which the estimator is highly non-linear. As a result it is necessary to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Their method outperforms several standard pitch tracking algorithms for speech, suggesting potential practical benefits of an approximate Bayesian treatment. For monophonic speech, a Kalman filter based pitch tracker is proposed by [16] that tracks parameters of a harmonic plus noise model (HNM). They propose the use of Laplace approximation around the predicted mean instead of the extended Kalman filter (EKF).…”
Section: A Music Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their method outperforms several standard pitch tracking algorithms for speech, suggesting potential practical benefits of an approximate Bayesian treatment. For monophonic speech, a Kalman filter based pitch tracker is proposed by [16] that tracks parameters of a harmonic plus noise model (HNM). They propose the use of Laplace approximation around the predicted mean instead of the extended Kalman filter (EKF).…”
Section: A Music Transcriptionmentioning
confidence: 99%
“…The sinusoidal model [30] is often a good approximation that provides a compact representation for the periodic component. The transient component can be modelled as a correlated Gaussian noise process [16], [20]. Our signal model is also in the same spirit, but we will define it in state Fig.…”
Section: A Modelling a Single Notementioning
confidence: 99%
“…However, the pitch values in a sequence are usually highly correlated, This work was funded by the Villum Foundation 1 , the Cluster of Excellence 1077 "Hearing4all" by the German Research Foundation (DFG) 2 , and the Danish Council for Independent Research, grant ID: DFF 1337-00084 3 . which motivates the development of the Bayesian methods to optimally use the correlations. The Bayesian methods incorporate prior distributions, and can be used to derive the minimum mean square error (MMSE) estimator and the maximum a posteriori (MAP) estimator [6], e.g., [7].…”
Section: Introductionmentioning
confidence: 99%
“…denote the eigenvalues of the matrix , in which is the sample covariance matrix and is an matrix whose columns are orthogonal to such that defines a complete orthonormal basis, which satisfies (6) In the Appendix, it is shown that in a single snapshot case, i.e., , the likelihood function is given by (7) where is the measurement vector in the single snapshot case. The model under hypothesis , presented in (2), is equivalent to (4), with a single snapshot, i.e., .…”
Section: A : Harmonic Noisementioning
confidence: 99%
“…In the single snapshot case where , the sample covariance matrix is given by and the matrix can be rewritten as (24) Since the matrix is of rank one, then its eigenvalues are equal to zero except the first one, , given by (25) According to (6), , and thus,…”
Section: Appendix Derivation Of the Likelihood Function In (7) For Thmentioning
confidence: 99%